PERAN LEMBAGA PERLINDUNGAN SAKSI DAN KORBAN (LPSK) DALAM PERLINDUNGAN HUKUM TERHADAP ANAK SEBAGAI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL (STUDI DI PROVINSI GORONTALO) - Putri Nur Rizki Patahila Lahabu; Irwansyah Reza Mohammad; Salahudin Pakaya (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2026)
This study examines the ineffectiveness of the Witness and Victim Protection Agency (LPSK) in providing legal protection for child victims of sexual violence in Gorontalo Province. Based on victimology theory, ideal protection should be proactive, comprehensive, and focused on victim recovery. However, findings in the field indicate a significant gap between theory and practice. The LPSK’s implementation of protection is reactive, partial, and delayed, driven by informal coordination with the Women’s Empowerment and Child Protection Agency (DP3A). The LPSK, headquartered in Jakarta, only gets involved after a case escalates, creating dangerous bureaucratic delays and leaving victims vulnerable. The root of the problem is the lack of LPSK representative offices in the regions, which is exacerbated by internal factors such as limited budgets, as well as external factors such as low socialization, weak inter-agency coordination, and social stigma. This study concludes that this ineffectiveness is a complex, systemic problem, necessitating strategic measures such as establishing a LPSK representative office in Gorontalo, strengthening the budget, intensive outreach, and formalizing inter-agency synergy through joint Standard Operating Procedures (SOPs) to achieve optimal protection in accordance with the principles of victimology.